Possibilities alternative grain production in the highlands area of Central Serbia - Glamočlija, Đorđe; Staletić, Mirjana; Ikanović, Jela; Spasić, Marija; Đekić, Vera; Davidović, Marija (Economics of Agriculture, 2018)
Two-year investigations of possibilities production of alternative grains (buckwheat, quinoa, triticale and spelt) were carried out at fve sites hilly-mountainous regions of Serbia. These are around Valjevo in western Serbia, Nova Varos and Pozega in southwestern Serbia, in Kucajna village (municipality Kucevo) and Zajecar in eastern Serbia. Results from experimental felds in Stara Pazova (Srem) served as control. The alternative grains are grown using standard agricultural technology used in commercial production. Mineral fertilization and crop protection with pesticides are not carried out. Weeds are suppressed by hand during vegetation period. The largest grain yields per unit area were obtained on the test trials at soil chernozem type in Srem. However, the results achieved in less fertile soil on hilly-mountainous regions of Serbia and changed agroecological conditions indicate that these plants can be successfully grown in less favorable conditions for agricultural production. This is of particular importance for small rural households, which would changing the sowing structure signifcantly increase the production per unit area as an alternative grain products greatly appreciated to make high-quality and healthy food. As the demand for these products continue to rise on the world market, we should look for an opportunity for improvement of our rural areas where there are natural resources for the production of these feld crops.